Business financial information secrets : how a business produces and utilizes critical financial information - Tracy, Tage C. (John Wiley & Sons, Inc., 2021)
"To succeed in today's business world, you must understand critical financial information on your internal management. Business Financial Information Secrets is focused on the internal producers and users of financial statements/information (from the inside out). If you don't understand cash flows you fail to understand the lifeline/blood line of a business. Fail here, and your business will ultimately fail. Business Financial Information Secrets is the companion book to How to Read Financial Reports. They are designed to be consumed/digested together to gain the most complete and comprehensive understanding of how businesses produce and report financial information. Topics include: - The What and When of Producing Best in Class Financial Information - Understanding the Flow of and Where Financial Information Originates - How to Analyze Financial Information and Its Meaning - Why Financial Information is So Critical and How to Use it to Your Advantage."--